Enhancing lactation through oxytocin massage and breast care - Kristina Sanadi; Dewi Mayangsari; Sa'adah Mujahidah (CV. LINK Education Publication, 2025)
Introduction: Breast milk is the best diet for infants because it includes nutrients that help them grow and thrive. Indonesia's exclusive breastfeeding coverage in 2022 was only 67.96%, down from 69.7% in 2021. Many factors contribute to low breastfeeding coverage in Indonesia, which has fallen short of the government target. In 2023, 29.1% of the newborns at Fakfak Health Centre were exclusively breastfed. Objectives: The study's goal was to see how much oxytocin massage and breast care helped postpartum women produce more breast milk. Methods: Quantitative research was conducted using an experimental design with a posttest alone procedure and a control group. The study included 28 maternity mothers. This study utilized SOP oxytocin massage and breast care, along with observation sheets. The Wilcoxon test used analysis data. Results: Breastfeeding women's average oxytocin massage intervention value increased by 5.71. The average value of the breast care intervention for nursing mothers increased by 6.21%. Breast care and oxytocin massage differed in their ability to increase breast milk fluency. The group following breast care had a median value of 8.00 with a p-value of 0.000 < 0.05, whereas the group following oxytocin massage treatment had a median value of 8.00. Conclusion: The breast care technique outperforms the oxytocin massage technique in terms of breast milk production.